Conceptual design of integrated seismic and energy retrofit interventions. (June 2021) - Menna, Costantino; Del Vecchio, Ciro; Di Ludovico, Marco; Mauro, Gerardo Maria; Ascione, Fabrizio; Prota, Andrea
Abstract: Nowadays, most of the Italian existing reinforced concrete (RC) buildings have become obsolescent and not compliant with modern requirements in terms of seismic safety, energy efficiency and living comfort. Many of them require a deep renovation to comply with minimum acceptable targets. In the last decade, major economic resources have been invested for the reduction of energy consumption and polluting emissions, while neglecting structural safety. Recent Italian seismic events brought out the high seismic vulnerability of residential and school buildings, which exhibited severe damage or collapse, thereby yielding significant social and economic losses. Therefore, an effective renovation process should consider, simultaneously, both structural and energy aspects. This research work presents a novel conceptual design methodology for the integrated structural and energy retrofit of existing RC buildings. It allows the definition of incremental strategies for integrated retrofit solutions with an increasing impact while taking into account overall structural and energy performances, costs and benefits. The applicability of the proposed methodology is illustrated with reference to two case studies RC buildings. The outcomes of this study can be used to help the stakeholders for the selection of the most effective and compatible retrofit solutions for a given set of performance targets. Highlights: In the last decades major investments were made for the reduction of energy consumption while neglecting structural safety. A novel methodology for the integrated structural and energy retrofit of existing RC buildings is presented. Integrated retrofit solutions with increasing impact, increasing cost and with compatibility among techniques are proposed. The outcomes of this study can be used for the selection of the most effective and compatible retrofit solutions.